PENGARUH ADOPSI AKUNTANSI TRANSAKSI ASURANSI SYARIAH BERDASARKAN PSAK 108 TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA AJB BUMIPUTERA 1912 WILAYAH SYARIAH JAKARTA) - Nuro Sholihah (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
This study aims to identify and analyze "Insurance Transaction Accounting Influence Adoption of PSAK 108 Against Sharia Based Financial Performance (Case Study At AJB Bumiputera 1912 Jakarta Regional Sharia)". The population in this study were all employees of all branches of sharia region of Jakarta as many as 84 people. The samples were set at 70 sample respondents with random sampling techniques, and data collection by questionnaire. Technical analysis of data using SPSS 20 to process the data from respondents who provide an assessment of the questionnaire stated in figures in the Likert Scale. Based on the results of the analysis showed that the presence of a negative influence between the application of the system in the early engakuan PSAK 108 on financial performance at the company AJB Bumiputera Sharia Jakarta region. This research proved the positive influence between the application of the measurement system in PSAK 108 on financial performance at the company AJB Bumiputera Sharia Jakarta region. This research proved the positive influence between the application of PSAK 108 in a presentation system on financial performance at the company AJB Bumiputera Sharia Jakarta region. This research proved the positive influence between the application of the system disclosure under PSAK 108 on financial performance at the company AJB Bumiputera Sharia Jakarta region